2012
DOI: 10.1186/1476-511x-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Role of extrathyroidal TSHR expression in adipocyte differentiation and its association with obesity

Abstract: BackgroundObesity is known to be associated with higher risks of cardiovascular disease, metabolic syndrome, and diabetes mellitus. Thyroid-stimulating hormone (TSHR) is the receptor for thyroid-stimulating hormone (TSH, or thyrotropin), the key regulator of thyroid functions. The expression of TSHR, once considered to be limited to thyrocytes, has been so far detected in many extrathyroidal tissues including liver and fat. Previous studies have shown that TSHR expression is upregulated when preadipocytes diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 24 publications
6
80
0
8
Order By: Relevance
“…Previous studies have confirmed that there might be a direct effect of TSH in the adipose tissue via adipocyte TSH receptors (TSHr) [34, 35] independently of its effect on thyroid function. Previously, TSH acting on TSHr has been shown to be involved in regulating lipolysis in neonates [36], inducing adipogenesis in mouse embryonic stem cells [37], directly stimulating leptin secretion in human adipose tissue [38], and inducing differentiation of preadipocytes [39], supporting the hypothesis that there is a relationship between adipose tissue and TSH. In theory, the regulation of thyroid function could be impaired due to a reduction of TSHr in the adipose tissue of obese individuals.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have confirmed that there might be a direct effect of TSH in the adipose tissue via adipocyte TSH receptors (TSHr) [34, 35] independently of its effect on thyroid function. Previously, TSH acting on TSHr has been shown to be involved in regulating lipolysis in neonates [36], inducing adipogenesis in mouse embryonic stem cells [37], directly stimulating leptin secretion in human adipose tissue [38], and inducing differentiation of preadipocytes [39], supporting the hypothesis that there is a relationship between adipose tissue and TSH. In theory, the regulation of thyroid function could be impaired due to a reduction of TSHr in the adipose tissue of obese individuals.…”
Section: Discussionmentioning
confidence: 81%
“…WAT cells were isolated from the inguinal pads of adult mice by collagenase treatment and stained with BODIPY neutral lipid probe and Alexa fluor 647-labeled antibody to Tshr; Tshr was used as a cell surface marker of adipogenesis, since its expression increases during adipogenesis (18,31).…”
Section: Resultsmentioning
confidence: 99%
“…In subjects with higher TSH, different processes in adipose tissue such as adipogenesis, lipogenesis, and lipolysis could be perturbed. Thyrotropin stimulates adipogenesis by activation of preadipocyte differentiation, and increases adipocyte hypertrophy by triglycerides synthesis in mature adipocytes via TSHR expressed in adipose tissue [25]. This might explain the pathogenesis of accumulation of visceral adipose tissue mass in subclinical hypothyroid women.…”
Section: Prace Oryginalnementioning
confidence: 99%